BAMBOO VALUE ADDED AND DEVELOPMENT STRATEGY ANALYSIS IN ANGKLUNG BUSINESS (CASE STUDY: CRAFTSMEN OF RAJA ANGKLUNG IN BANJAR CITY, WEST JAVA) - Cecilia Dewi, Riezca
Bamboo is a multipurpose, non-timber forest product used for various purposes. There are currently many businesses involved in the processing of bamboo into finished products, ranging from small and medium-sized industries to household businesses. The business of processing and utilizing bamboo can empower the community and create high value in the products. One of the bamboo processing centers in West Java is in the city of Banjar, which is famous for angklung, namely the Pengrajin Raja Angklung. Raja Angklung produces various types of angklung made of raw materials such as rope bamboo (Gigantochloa apus) and black bamboo (Gigantochloa atroviolaceae). This study will analyze the value added to the processing of bamboo into angklung and formulate a business development strategy for Pengrajin Raja Angklung. The method used in this study is a case study that focuses on one of the Angklung craftsmen. Data analysis included cost structure analysis and added value analysis using the Hayami Method. The sustainability of the business was then analyzed by looking at the value-added ratio, the share of labor, and profit levels. Raja Angklung’s internal and external factors were subjected to a business environment analysis. A business development strategy is developed through a SWOT-AHP analysis. The results showed that the cost structure analyzed gave the results of calculating the profit from the sale of angklung in Raja Angklung, which was Rp424,271,000 with R/C > 1 (2.56), which means this business is profitable. Hayami's added value analysis shows that angklung products made from rope bamboo and black bamboo have an added value of IDR54,000 per bamboo stick unit (86.40%) and IDR76,000 per bamboo stick unit (86.86%). Based on three criteria for business sustainability indicators, Raja Angklung has a high level of business sustainability, which is equal to 7. Furthermore, internal environmental analysis includes factors of production (raw materials, processes, and product output), marketing, finance, management, research and development, and analysis. The external environmental analysis includes socio-economic factors, technology, government, business competition for Raja Angklung. Analysis of production factors for bamboo raw materials and products shows that for the physical characteristics of rope bamboo raw materials have a moisture content value of 16.12%, a density of 0.71 gr/cm3, and a shrinkage of 1.66% in thickness dimensions, whereas black bamboo raw materials have a moisture content of 17.16%, a density of 0.63 gr/cm3, and a thickness shrinkage of 1.85%. The results of the acoustic test show that the musical tone of Raja Angklung products is in accordance with international music tone standards (ISO 16: 1975 Acoustics – Standard tuning frequency). The SWOT analysis shows that the main internal factor of strength is Raja Angklung’s bamboo raw materials, which are in accordance with raw material standards for Angklung, and the main weakness is the financial bookkeeping, which has not been carried out in detail. The external factor that becomes the main opportunity is that Raja Angklung can increase the income and welfare of the community around the business location, and the main threat is that there are many similar products at lower prices. Building cooperation with various parties, regular promotions in social media, making brochures and selling angklung in the e-commerce, increasing production capacity, using ovens for drying, and making product innovation, forming a business organizational structure, and market development and expansion by opening outlets are the priorities of Raja Angklung’s business development strategy, from main to last.